Level of customer satisfaction on online banking services provided by domestic and foreign commercial banks in Kuching - Lim, Ann Chee, Angelia (Universiti Malaysia Sarawak (UNIMAS), 2014)
This study determines the level of customer satisfaction on online banking services provided by domestic and foreign commercial banks in Kuching, Sarawak. The banks involved in this study are Maybank, Public Bank, Ambank, UOB, Standard Chartered, and HSBC. The customer satisfaction of online banking services are determined by using survey method whereby questionnaires are distributed randomly to bank customers in Kuching. The findings of this study show the evidence of customer satisfaction and help the banks to determine the most influencing dimensions in determining customer satisfaction. There are also recommendations by the end of the study which may help the future researchers in similar studies.